Enganging Secularization with Expository Preaching - Frederich Oscar Lontoh (Jurnal Didaskalia, 2019)
This research trying to see the phenomenon of secularization that is dominating the world. Some people argue that secularization is dangerous for the Christian faith while some say that it is just the opposite that secularization is necessary. What is developing now is that secularization becomes a movement in personal thought. Some experts distinguish between secularization and secularism. Secularism is a kind of ideology that remove everything supernatural defining ones life. Secularism refers to the fact that religion has lost influence on the societal, the institutional and the individual levels. Preaching is a main part of church to educate the congregation about God, what His will and also supernatural being. Expository preaching is the method of teaching scripture. There are many other ways to preach a sermon that are beneficial to a congregation. However, that these other forms of preaching should never replace expository preaching in the life of the church. Solid expository preaching brings scripture to life. It connects the meaning of the passage to the life of the hearer, helping them to apply what they’ve heard to their specific life situations. This is the way to maintain people from leaving God and supernatural being in modern human life.